A Structural Equation Model for the Study of Education Supply Chain Management Practices in Private Universities in Malaysia - Basu Govindaraju; John Jeyasingam; Md. Mamun Habib; Uvarani Letchmana (International Journal of Supply Chain Management, 2020)
Abstract: Structural Equation Modeling (SEM) is a method that is frequently applied by business researchers to assess empirically new theoretical proposals articulated by means of complex models. Hence in this study SEM was engaged to scrutinize the impact of SCM practices on the performance of higher education in Malaysia. Firstly, the SCM practices survey was designed to investigate the main factors which influence supply chain practices in universities in Malaysia. Amongst the pool of constructs include: customer relationship, supplier relationship, information technology, information sharing, and innovation. Next, based on the SEM, the intensities of SCM practices of the universities were quantified in accordance with those constructs. The findings were supported by empirical evidence, as the study established that only information sharing and information technology had a significant positive relationship and impact on the universities performance. This paper provides a greater understanding of the interactions between the key elements of SCM practices associated with university performance and their impact on universities in Malaysia. Keywords: SEM, SCM practices, constructs, University Performance.